1995
DOI: 10.1149/1.2044282
|View full text |Cite
|
Sign up to set email alerts
|

The Autocatalytic Deposition of Gold in Nonalkaline, Gold Thiosulfate Electroless Bath

Abstract: The autocatalytic deposition of gold has been investigated in a novel, nonalkaline, noncyanide electroless gold plating bath. The bath consists of sodium L-ascorbic acid as the reducing agent and sodium gold (I) thiosulfate as the gold complex. Ascorbic acid autocatalytically reduces gold thiosulfate at deposition rates of approximately 1 ~m/h. The reaction sequence includes various side reactions responsible for consuming reactants and lowering the deposition rate. The rate of the electroless gold thiosulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 6 publications
0
43
0
Order By: Relevance
“…Electrowinning is also an option for gold recovery, and [Au(S 2 O 3 ) 2 ] 3− anions in the pregnant solutions will migrate to the cathode, being reduced to metallic gold [64][65][66][67]. However, it is also not a feasible choice because undesirable reactions of other anions including copper (I) thiosulfate complexes, sulfur-oxygen anions and other metal thiosulfate complexes in the solutions can occur on the electrode surface.…”
Section: High Requirements On the Solution Ph Values Resin Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrowinning is also an option for gold recovery, and [Au(S 2 O 3 ) 2 ] 3− anions in the pregnant solutions will migrate to the cathode, being reduced to metallic gold [64][65][66][67]. However, it is also not a feasible choice because undesirable reactions of other anions including copper (I) thiosulfate complexes, sulfur-oxygen anions and other metal thiosulfate complexes in the solutions can occur on the electrode surface.…”
Section: High Requirements On the Solution Ph Values Resin Adsorptionmentioning
confidence: 99%
“…Ammonia-free thiosulfate leaching process by Barrick Gold Corporation to treat a carbonbearing sulfide gold ore pretreated with acidic or alkaline pressure oxidation [4,5]. [64][65][66][67] Low current efficiency and high energy consumption due to the undesirable reactions Difficulty in cyclic utilization of pregnant thiosulfate solutions…”
Section: Introductionmentioning
confidence: 99%
“…In this system, the enediol group of ascorbic acid is catalytically oxidized to dehydroascorbic acid at the gold surface. 24 The generated electrons then reduce Au 1+ from TPN-Au-AMT that is adsorbed on the gold surface to metallic Au 0 and TPN and AMT are released. The reaction results in the self-perpetuating deposition of gold on gold surfaces or autocatalytic gold deposition.…”
Section: Resultsmentioning
confidence: 99%
“…Kohl (1995, 1997) have demonstrated that the gold reduction performance in a thiosulfate bath was comparable to a cyanide bath, electrochemically. 56,57) Stripped resin is regenerated by a 10 vol% HCl solution and recycled back to the gold adsorption stage.…”
Section: Feasibility Of Perchlorate Elution Processmentioning
confidence: 99%